The Relationship between Cormic Index and Mode of Delivery - Maryam Pourshirazi; Nahid Golmakani; Habibollah Esmaeili; Samira Ebrahimzadeh Zagami; Fatemeh Tara (Mashhad University of Medical Sciences, 2017)
Background & aim: The risks of maternal mortality and morbidity associated with cesarean delivery are three and two times higher than vaginal delivery, respectively. The majority of cesarean sections are due to failure to progress in labor. One of the common risk factors for failure to progress is small maternal body size. Cormic index is an indicator of body composition assessment, which estimates trunk and leg length. In this study, we aimed to investigate the relationship between Cormic index and mode of delivery. Methods: This descriptive, cross-sectional study was performed on 170 pregnant women referred to Omolbanin Hospital of Mashhad, Iran. Standing and sitting heights were measured at the onset of active phase of labor. Cormic index was calculated as sitting height/standing height×100. Mode of delivery was followed and recorded. Kruskal-Wallis and Bonferroni-corrected Mann-Whitney tests were performed, using SPSS version 16. Results: The mean Cormic index was 52.04±2.85. There was a significant relationship between mode of delivery and Cormic index, sitting and standing heights, and leg length measures. However, there was no significant relationship between body mass index and mode of delivery. Conclusion: Our findings indicated that mode of delivery is associated with Cormic index. With high Cormic indices (long trunk and short legs) the rate of assisted delivery rose compared to vaginal and cesarean deliveries.